Analisis Efektivitas Dan Efisiensi Distribusi Beras Miskin (Raskin) Di Kecamatan Trienggadeng Kabupaten Pidie Jaya - M. Dian Septian; T. Saiful Bahri; T. Makmur (Jurnal Agrisep, 2013)
ABSTRACT. Raskin Program is a national program that has direct contact with the public . Through this program, the government provides assistance to the community to gain the right to food. There are six problems in the distribution of Raskin , so it is very detrimental to society. First, the wrong target . Second , the amount of rice distributed is less with what has been programmed , Third , data on the number of poor families errors . Fourth , the price is not in accordance with the initial plan . Fifth, there was a delay in receiving Raskin rice . Sixth , poor quality rice. The analytical method used was based on the price at the retail level (households ), Furthermore, the level of effectiveness and efficiency Distribution (Ed). The effectiveness of the distribution of Raskin program is not effective where the level of effectiveness of the distribution of Raskin at 39.69 % . While the level of efficiency of the distribution of Raskin program efficiently in the category in which the value of the efficiency of the distribution equal to the lesser of 50 % with a value of 4.22%.